Enhancing the detection of out-of-hospital cardiac arrest: a study of emergency medical system in Thailand - Tippayanate, Nantawan; Phonkanya, Patchalee; Nuangkantee, Kanokwan; Nuangkantee, Kamonchanok; Raksapakdee, Kwansiri; Boonnop, Watcharaporn; Jitsuwan, Natlada (International Journal Of Community Medicine And Public Health, 2023)
Background: Globally, survival rates for out-of-hospital cardiac arrest remain low. Implementing a dispatch-assisted cardiopulmonary resuscitation protocol in evolving emergency medical services systems has shown potential for improving OHCA detection and reducing the time to initiate chest compressions. Methods: In this study, audio recordings of OHCA emergency calls from different regions of Thailand were analyzed from January 2021 to December 2021. The study aimed to assess OHCA detection efficiency and provide CPR recommendations, including OHCA discrimination rates, time from call initiation to OHCA identification, and time to start CPR following dispatcher guidance. Results: There were 280 OHCA cases, with 170 (60.7%) successfully identified and excluded by dispatchers. OHCA detection took an average of 39 seconds (compared to a benchmark of 60 seconds), while the mean time from notification to chest compression initiation was 298 seconds (compared to a benchmark of 220 seconds). However, OHCA discrimination and phone-based resuscitation advice were highly sensitive (81.18%), accurate (85.72%), and specific (92.73%). Conclusions: OHCA presents challenges, with the need for faster CPR initiation. Improving reporting processes, enhancing caller understanding, and refining dispatcher skills are crucial to enhance OHCA detection and DA-CPR, ultimately improving survival rates.